Memorandum of Understanding between the Faculty of Arts, Monash University, Australia and Centre for Governance Studies, BRAC University, Bangladesh on academic and research collaboration (2006) - Faculty of Arts, Monash University; Centre for Governance Studies, BRAC University (Faculty of Arts, Monash University and Centre for Governance Studies, BRAC University, 2013)
The Faculty of Arts, Monash University and Centre for Governance Studies, BRAC University have agreed to the certain protocols governing their collaboration on academic and research-related activities.